PENGARUH AROMATERAPI BUNGA LAVENDER TERHADAP KUALITAS TIDUR LANSIA DI RSU Dr. WAHIDIN SUDIRO HUSODO MOJOKERTO - Khotimah, Siti; Nur So’emah, Eka (JURNAL KEPERAWATAN BINA SEHAT, 2015)
The fulfillment of people are known from quantity and quality of their sleeping. Sleeping quantity is the timing and sleeping amount person who is calculated by amount of time (hours). Sleeping quality is satisfaction someone to sleep, so that someone does not show a tired feeling, stimulating easily, anxious, lethargic and apathetic, blackish around eyes, swollen eyelids, red conjunctiva, sore eyes, fragmented attention, headaches, and sleepy. Sleeping quality problem is a situation where someone is not satisfied to sleeping needed. One way to overcome sleeping quality problem uses aromatherapy lavender flowers . Lavender contain linalyl acetate which is effective for releases work system, relaxes the nerves, and sinews muscles that are tense. The puspose of this research showed the influence of aromatherapy lavender flower beds to the quality of the elderly. The design was Pre design Experiment one group pre and posttest design. The sample was chosen by Purposive Sampling. The sample of this research was 16 people elderly. Measuring instrument used a questionnaire PSQI (Pittsburgh Sleep Quality Index). The result of Wilcoxon test statistic indicated P Value = 0.001 was less than α = 0.05 which means there was influence of aromatherapy lavender flower on sleeping quality of elderly.Keyword: Elderly, Sleeping Quality, Aromatherapy Lavender Flowers